Israeli Bourekas films : their origins and legacy - Kimchi, Rami (Indiana series in Sephardi and Mizrahi studies., 2023)
"A genre of comic melodramas produced in the 1960s and '70s, Bourekas films are among the most popular films ever made in Israel. In Israeli Bourekas Films, author and filmmaker Rami Kimchi sets out a history of Bourekas films and discusses their origin. Kimchi considers the representation of Sephardi or Mizrahi Jews in the films, noting that the material culture reflected in the the films presented a culture that was closer to the European Yiddish culture than to the Middle Eastern world of the Mizrahim. Kimchi reflects on the enormous popularity and commercial success of Bourekas films, uncovers how they were made, who made them and why, and discusses the impact of the films on Israeli cinema today. Israeli Bourekas Films is a film insider's view of the characters, stories, and cultures that made Bourekas films such an important part of Israeli life"--